Exploring the Communication Role in Total Quality Management Implementation in Educational institution - Rosida Kerin Meirani; Achmad Supriyanto (Budapest International Research and Critics University, 2022)
This study aims to determine the role of communication, communication process, and effective communication in the implementation of TQM in educational institutions. This research is a literature study with a descriptive qualitative method. The research was conducted by reviewing some relevant literature, then analyzed to get some formulation of the research results. The final step is the evaluation and withdrawal of conclusions as a result of the final research. This study shows that the communication process in the implementation of TQM in educational institutions occurs by involving communication components that include sender, message, receiver dan media. Furthermore, effective communication in the implementation of TQM occurs if the message conveyed is not only understood but also implemented as desired. Finally, the role of communication in the implementation of TQM in educational institutions is as a liaison or facilitator of each element of TQM. Further research is expected to explain in more detail the process and strategy of effective communication in the implementation of TQM, especially in educational institutions.